A proposal for engaging a stakeholder panel in planning post-mining land uses in Australia's coal-rich tropical savannahs. (December 2018) - Everingham, Jo-Anne; Rolfe, John; Lechner, Alex Mark; Kinnear, Susan; Akbar, Delwar
Highlights: Focuses on processes for returning rehabilitated coal lands to grazing uses. Characterises opportunities and barriers for returning post-mining land to grazing. Endorses involving stakeholders in determining acceptable uses for post-mining land. Proposes a deliberative process with panels of a cross-section of stakeholders. Proposes 'utility' as a goal of mine rehabilitation and closure in Queensland. Abstract: In Queensland's Bowen Basin, a major Australian coal reserve, areas of post-mining land are increasing. These areas have been subject to decades of coal-mining and, without appropriate transfer to alternative use, may remain as vacant land unable to be used for grazing or other productive uses. Research that informs new and revised policies and processes to optimize rehabilitation and post-mining land use planning is critical in assisting regional economies to transition to post-mining contexts. This paper explores the potential for panels comprised of stakeholders to agree on a beneficial land use, which is one of the four goals of mine rehabilitation and closure specified by the Queensland regulator. Whilst current guidelines require stakeholder consultation, there is little real evidence that rehabilitation and closure planning processes incorporate the perceptions of potential future land users in terms of the utility of ex-mining leases, socio-economic value and associated opportunities and risks. In contrast, existing literature reveals the range of influencing factors that landholders, especially graziers, may consider in determining the utility and value proposition of land packages. These include physical, agronomic, ecological, economic, aesthetic and recreational characteristics. This gives rise to two questions: (i) what role(s) can input from stakeholders and potential future land users play in considering the opportunities and barriers to incorporating ex-mine land into grazing properties; and (ii) what are the characteristics of an appropriate model for engaging and empowering a stakeholder panel to play those role(s)? This research identifies a potential role for stakeholders in adaptive management in collaboration with regulators and mining companies, via a process of long-term engagement among a cross-section of predominantly local people. Visual models of an authentic example are proposed as the basis for reaching agreements about the land use challenge and reconciling ecosystem, social and economic functions and values. This research thereby provides a narrative on both of the research questions raised and proposes a re-conceptualisation of rehabilitation goals in order to optimize post-mining futures.